2014
DOI: 10.1111/nph.13245
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of barley plants to low Pi leads to rapid changes in root respiration that correlate with specific alterations in amino acid substrates

Abstract: SummaryThe majority of inorganic phosphate (P i ) stress studies in plants have focused on the response after growth has been retarded. Evidence from transcript analysis, however, shows that a P i -stress specific response is initiated within minutes of transfer to low P i and in crop plants precedes the expression of P i transporters and depletion of vacuolar P i reserves by days.In order to investigate the physiological and metabolic events during early exposure to low P i in grain crops, we monitored the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Recent metabolic studies have suggested a role for dicarboxylates in rapid respiratory responses to Pi starvation, and DICs are indeed induced within 1 h of transfer of plants to Pi depleted medium (Lin et al, 2011;Alexova et al, 2015). Rapid transcriptional responses within 10 min have also been found in response to high-light treatment and involve chloroplast-located triose phosphate/phosphate translocator (TPT; Vogel et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recent metabolic studies have suggested a role for dicarboxylates in rapid respiratory responses to Pi starvation, and DICs are indeed induced within 1 h of transfer of plants to Pi depleted medium (Lin et al, 2011;Alexova et al, 2015). Rapid transcriptional responses within 10 min have also been found in response to high-light treatment and involve chloroplast-located triose phosphate/phosphate translocator (TPT; Vogel et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, false-positive sequencing results from high-throughput sequencing methods can occur and have been described in recent literature. Putative mechanisms that have been suggested include low-level contamination, sequence errors introduced during PCR (to generate amplicons) or sequencing, and oxidation of DNA during the library preparation step [ 37 , 38 , 39 , 40 ]. The latter two issues have the potential to introduce nucleotide polymorphisms that could affect taxonomic designations.…”
Section: Discussionmentioning
confidence: 99%
“…(FW) h À1 (Alexova et al, 2015;Scafaro et al, 2017) ATP produced by respiration (O 2 consumption) ATP : O 2 is 4.5 (Box 2) Root surface area : FW ratio: 70 cm 2 g À1 (FW) (W. Fricke, pers. com.)…”
Section: Standard Units and Conversionsmentioning
confidence: 99%